Estrategias metodológicas y su impacto en la comprensión lectora en los estudiantes de la UE Ana Rosa Valdivieso de Landívar, Ventanas. 2022 - Moreira Contreras, Eva Juliana (2023)
This research Project is aimed at the area of language and literatura in order to mediate on the methodological strategies and their impacto n the Reading comprehension of the educational unit Ana Rosa Valdivieso de Landivar of the canton ventanas, having as fundamental objetive of the investigation to determine the way in which the methodological strategies impact Reading comprehension, while among the secondary onjectives we have to identify the characteristics that the methodological strategies present, through the following instruments: a survey and an observation sheet, through the progress of the investigation, the background of the methodological strategies is exposed, the theoretical foundations that are used in the classroom associated with the forms and strategies of student learning, in the same way that a detailed analysis of the importance is increased. Of the implementation of these methodological strategies and their impact on Reading comprehension, several techniques and factors that influence the result of Reading comprehension are highighted, consideration is also made about the advantages of a good rading comprehension and the disadvantages of not having a good development of Reading comprehension, through this research Project it is expected to contribute to the improvement of the development and academic performance of students.